The Role of Cyclic Nucleotides in Pituitary Lactotroph Functions - Kucka, Marek; Bjelobaba, Ivana; Tomic, Melanija; Stojilkovic, Stanko (Frontiers in Endocrinology, 2013)
Lactotrophs are one of the five secretory anterior pituitary cell types specialized to synthesize and release prolactin. In vitro, these cells fire action potentials spontaneously and the accompanied Ca2+ transients are of sufficient amplitude to keep the exocytotic pathway, the transcription of prolactin gene, and de novo hormone synthesis continuously active. Basal cyclic nucleotide production is also substantial in cultured cells but not critical for the action potential secretion/transcription coupling in lactotrophs. However, elevated intracellular cAMP levels enhance the excitability of lactotrophs by stimulating the depolarizing non-selective cationic HCN and background channels, whereas cGMP inhibits it by activating Ca2+-controlled K+ channels. Elevated cAMP also modulates prolactin release downstream of Ca2+ influx by changing the kinetic of secretory pores: stimulate at low and inhibit at high concentrations. Induction of prolactin gene and lactotroph proliferation is also stimulated by elevated cAMP through protein kinase A. Together these observations suggest that in lactotrophs cAMP exhibits complex regulatory effects on voltage-gated Ca2+ influx and Ca2+-dependent cellular processes.